The crossed-leg position increases the dimensions within the acoustic target window for neuraxial needle placement in term pregnancy: a prospective observational study. (November 2020) - Sharma, M.; Qasem, F.; Sebbag, I.; Jones, P.M.; Singh, S.I.
Highlights: Investigation of lumbar sonographic changes in the crossed-leg position. Positioning pregnant women cross-legged improved the acoustic window. Structures within the acoustic window increased in length by a mean of 1.4–2.2 mm. Sitting cross-legged did not impair comfort in comparison to the standard position. Ease of needle placement in the crossed-leg position needs to be investigated. Abstract: Introduction: Neuraxial anesthesia in obstetric patients may be difficult to achieve due to anatomical changes in pregnancy. The crossed-leg position may help in optimizing patient position. We prospectively evaluated the utility of the crossed-leg position compared with a standard position using ultrasound measurements. Methods: Thirty women with term singleton pregnancy admitted for vaginal delivery were recruited. Women with a history of spinal trauma or surgery, congenital spinal abnormality, advanced first stage of labor or a language barrier were excluded. Two anesthesiologists, blinded to each other's measurements, scanned each subject in the crossed-leg position and standard position. Measurements of the lengths of the posterior longitudinal ligament, ligamentum flavum and interlaminar distance were recorded at the L3-L4 interspace. Comfort level in each position was scored on a Likert Scale. Results: Twenty-nine women completed the study (complete data n=28). Significant increases were observed in the lengths of the posterior longitudinal ligament (mean difference 2.2 mm, 95% CI 1.3 to 3.2; P <0.001), ligamentum flavum (mean difference 1.4 mm, 95% CI 0.7 to 2.1; P <0.001) and interlaminar distance (mean difference 1.4 mm, 95% CI 0.4 to 2.5; P =0.006) in the crossed-leg position. No significant differences in comfort were observed. Conclusion: We demonstrated a significant increase in the sonographically measured lengths of the posterior longitudinal ligament, ligamentum flavum and interlaminar distance in the crossed-leg position when compared with the standard position. Both positions were comfortable. Further studies should explore whether these findings translate clinically into easier needle placement in the crossed-leg position.